Multimedia aided physical education - Vass, Z. (International Journal of Computer Science in Sport, 2002)
In the past few years multimedia is getting very popular using as a useful tool kit for teachers and students as well. That`s why we thought to create a multimedia CD for the Physical Education teachers, working in primary school. The basis of the CD is built on the Hungarian Physical Education system and it includes 4 different sport branches which are the followings: Track and Field, Soccer, Judo, Basketball. These four areas are very popular and well educated in Hungary. The aim of this CD is to give more motivate for the P.E. teachers to teach these sport branches often in the primary school. So in order to achieve our aims first of all we have organized the first international workshop on sport focusing on multimedia aided physical education in 6. XII. 2002.